Application in Gene Editing in Ovarian Cancer Therapy. (21st April 2022) - Luo, Shuang; Wang, Yujiao; Tao, Yongyu; Li, Shuo; Wang, Zirui; He, Wei; Wang, Hangxing; Wang, Nan; Xu, Jianwei; Song, Hailiang
Abstract: The onset and progression of ovarian cancer (OC) are closely related to dysregulated gene expression. Current treatments for OC are mainly limited to surgery and chemotherapy. However, due to low drug sensitivity, the prognosis OC is exceptionally poor and the recurrence rate remains high. Hence, it is vital to develop new treatment strategies. Gene editing for site-specific genomic modification is a powerful novel tool for the treatment of OC. In this article, current gene editing research for the treatment of OC is reviewed to provide a reference for the clinical application of new approaches to improve treatment outcomes and prognosis.